Quality and dry matter yield of triticale forage in winter and late-spring in Southwestern Spain - Rodrigo S.; Poblaciones M.J.; Pinheiro N.; Maças B.; Olea L.; Santamaría O.; García-White T. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Special soil and climate conditions of the dehesa ecosystem in the south west of Spain have an influence in herbaceous biomass production, causing moments with a lack of feed for extensive livestock along the year. In this paper the possibility to introduce triticale crop for a double use (by grazing or cutting in winter and cut at late spring) to cover winter and summer deficiencies in animal feed, has been studied. Triticale varieties were, var. Fronteira, var. Alter and two experimental cultivars from the Portuguese National Agricultural Research Institute, called INIA 1 and INIA 2. As control, a variety of Italian ryegrass, was used. The experiment was carried out in a dehesa in the SW of Spain during three years (2008-09, 2009-10 and 2010-11). On average some triticale cultivar (INIA 1 and INIA 2) biomass yields were similar to the reference treatment one, giving rye-grass the lowest biomass in dry years. Alter and INIA 2 did not show decrease in DM yield when a cut in winter was applied but show an increment in quality (high CP content and low NDF).
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)